1997
DOI: 10.1128/jvi.71.10.7541-7548.1997
|View full text |Cite
|
Sign up to set email alerts
|

Moloney murine leukemia virus-derived retroviral vectors decay intracellularly with a half-life in the range of 5.5 to 7.5 hours

Abstract: Replication-incompetent recombinant retroviruses are currently used for gene delivery. The limited efficiency of gene transfer using these vectors hampers implementation of gene therapy. Successful integration of Moloney murine leukemia virus (MMuLV)-derived retroviral vectors into the host cell DNA requires cell division. The time difference between virus entry and cell division is variable and prolonged in slowly dividing cells. Therefore, the rate of intracellular decay of internalized vectors between the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
2

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(30 citation statements)
references
References 34 publications
(43 reference statements)
1
27
0
2
Order By: Relevance
“…Figure 3B shows that the cell-cycle distribution did not change significantly for the first 8 hours after inoculation. During the first 4 hours, a small increase in the percentage of S-phase and a small decrease in the percentage of G 1 -phase cells was observed, i.e., the cells did not arrest and accumulate in G 1 for the first 6 hours of culture, as observed by Andreadis et al (1997). Here, we show no such perturbation of cell-cycle progression in the FLYRD18/LNC-hB7 cell line as a result of cell attachment.…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…Figure 3B shows that the cell-cycle distribution did not change significantly for the first 8 hours after inoculation. During the first 4 hours, a small increase in the percentage of S-phase and a small decrease in the percentage of G 1 -phase cells was observed, i.e., the cells did not arrest and accumulate in G 1 for the first 6 hours of culture, as observed by Andreadis et al (1997). Here, we show no such perturbation of cell-cycle progression in the FLYRD18/LNC-hB7 cell line as a result of cell attachment.…”
Section: Resultssupporting
confidence: 65%
“…Therefore, to measure virus titer produced in a particular cell-cycle phase, samples from separated cell fractions need to be taken within this time period. However, a number of groups have reported temporary inhibition of cell-cycle progression (up to 6 h) following the detachment of some cell types from the culture substratum (Andreadis et al, 1997;Campisi and Medrano, 1983). As mentioned above, if cell-cycle progression is essential for virus production, the cells need to be cycling immediately after inoculation to compare virus levels produced during the first few hours.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we cannot rule out the possibility that the intracellular degradation rates in actively replicating cells might be different than in stationary cells. Andreadis et al (1997) developed a method to quantify the intracellular stability of retroviral vectors in actively replicating cells without synchronization and estimated the intracellular half-life of MoMLV vectors inside NIH-3T3 cells to be 6.5 h. This method may be useful to better quantify the intracellular half-life of our retroviral vectors, since the serum starvation experiment indicated that intracellular degradation was non-negligible.…”
Section: Discussionmentioning
confidence: 99%
“…A sensitivity analysis of the model was performed by artificially raising by 10% each of the parameter values shown in Table I while keeping all of the other parameter values constant. Two different intracellular degradation rates were investigated: k di ¼ 0.0012 h À1 (Table I) (Andreadis et al, 1997) where intracellular degradation is increased, such as by the presence of host cell restriction factors. The results are shown in Figure 8.…”
Section: Discussionmentioning
confidence: 99%